A Revolutionary People At War : The Continental Army and American Character, 1775-1783 - Royster, Charles (Book collections on Project MUSE., 1979)
Discusses the role of the Revolutionary War--with its demands on courage, discipline, and dedication to the cause of freedom--on the shaping of America's national character.